Pandora hearts. 17 - Mochizuki, Jun (Yen Press, 2013)
"The earnest emotions of one man cross the divides of space and time, laying bare his life, which was long hidden in the depths of memory. But when these revelations come to pass, the reality Oz has known begins to change and shift into something wholly bewildering. Could the desire in one man's heart have been the very darkness gnawing at everything all along...?"--Page [4] of cover.